Transferrin-polycation conjugates as carriers for DNA uptake into cells. - Wagner, E (1990)
We have developed a high-efficiency nucleic acid delivery system that uses receptor-mediated endocytosis to carry DNA macromolecules into cells. We accomplished this by conjugating the iron-transport protein transferrin to polycations that bind nucleic acids. Human transferrin, as well as the chicken homologue conalbumin, has been covalently linked to the small DNA-binding protein protamine or to polylysines of various sizes through a disulfide linkage. These modified transferrin molecules maintain their ability to bind their cognate receptor and to mediate efficient iron transport into the cell. The transferrin-polycation molecules form electrophoretically stable complexes with double-stranded DNA, single-stranded DNA, and modified RNA molecules independent of nucleic acid size (from short oligonucleotides to DNA of 21 kilobase pairs). When complexes of transferrin-polycation and a bacterial plasmid DNA containing the gene for Photinus pyralis luciferase are supplied to eukaryotic cells, high-level expression of the luciferase gene occurs, demonstrating transferrin receptor-mediated endocytosis and expression of the imported DNA. We refer to this delivery system as "transferrinfection."